2008
DOI: 10.1086/589654
|View full text |Cite
|
Sign up to set email alerts
|

The Dartmouth Stellar Evolution Database

Abstract: The ever-expanding depth and quality of photometric and spectroscopic observations of stellar populations increase the need for theoretical models in regions of age-composition parameter space that are largely unexplored at present. Stellar evolution models that employ the most advanced physics and cover a wide range of compositions are needed to extract the most information from current observations of both resolved and unresolved stellar populations. The Dartmouth Stellar Evolution Database is a collection o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

72
2,190
3
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,712 publications
(2,286 citation statements)
references
References 63 publications
72
2,190
3
2
Order By: Relevance
“…The brightest objects at F606W = 22.5 - 23.5 represent the newly formed remnants of progenitor hydrogen--burning stars that just exhausted their nuclear fuel. The mass of the progenitor stars can be calculated accurately from stellar evolution models since the age of the population is well measured 9 . For Messier 4, this mass is M INITIAL = 0.802 (+0.007; --0.011) M SUN .…”
mentioning
confidence: 99%
“…The brightest objects at F606W = 22.5 - 23.5 represent the newly formed remnants of progenitor hydrogen--burning stars that just exhausted their nuclear fuel. The mass of the progenitor stars can be calculated accurately from stellar evolution models since the age of the population is well measured 9 . For Messier 4, this mass is M INITIAL = 0.802 (+0.007; --0.011) M SUN .…”
mentioning
confidence: 99%
“…4, there is some disagreement between our own results and those of Pecaut, Mamajek, & Bubar (2012). However, we note that the use of Pecaut, Table 2. combination of empirical isochrones and the models of Dotter et al (2008) and found an age for USco of 11±1 Myr. As seen in Fig.…”
Section: Evolutionary Status Of the Investigated Starsmentioning
confidence: 99%
“…7 A comparison among these population synthesis models and observations has been already performed by Noel et al (2013), and it was found that these models disagree -being in general too red -with the integrated colours of superclusters for ages between ∼ 10 8 and ∼ 10 9 years. than those of Pols et al (1995), which were implemented in Vazdekis et al (1996), and those of Dotter et al (2008) (see also An et al 2009). As their temperatures are higher the Padova00 VLM stars are brighter than the ones we employ here for the BASTI models (see figure 5 in Vazdekis et al 2012).…”
Section: Isochronesmentioning
confidence: 99%